Bone mineral density in women on long-term mud-bath therapy in a Salus per Aquam (SPA) environment - A. Loi; S. Lisci; A. Denotti; A. Cauli (PAGEPress Publications, 2013)
The objective of this study was to assess bone mineral density (BMD) in women on long-term mud-bath therapy (MBT) for osteoarthritis in a Salus per Aquam (SPA) environment. Two hundred and fifty female patients were randomly enrolled in this study in the SPA center of Sardara (Cagliari, Italy) where they were treated with a combination of daily full body mudpacks and bicarbonate-alkaline mineral water baths at cycles of 2 weeks/year. BMD was evaluated by means of calcaneus ultrasonometry (Sahara Hologic Inc., Bedford, MA, USA) and results analyzed according to duration of treatment and clinical variables. In the group of patients undergoing MBT for more than 10 years (group A) and for 3 to 10 years (group B) a reduced frequency of osteopenia and osteoporosis was detected (35.8% and 7.6% group A; 38.4% and 8.5% group B, respectively) compared to controls (group C) (48.9% and 23.4%, P<0.01 and P<0.001). Furthermore, higher T-score values were detected in group A and B (-1.05±1.28 and -1.24±0.94, respectively) compared to group C (-1.93±0.78) (P<0.0002 and P<0.0001). Similar results were observed in the analysis of data restricted to women in menopause only. Long-term mud-bath therapy in SPA environment appeared to be beneficial for BMD.